2009
DOI: 10.1128/jcm.01119-09
|View full text |Cite
|
Sign up to set email alerts
|

Cooccurrence of Predominant Panton-Valentine Leukocidin-Positive Sequence Type (ST) 152 and Multidrug-Resistant ST 241 Staphylococcus aureus Clones in Nigerian Hospitals

Abstract: Ninety-six clinical isolates ofStaphylococcus aureus is a major cause of both hospital-and community-acquired infections. In particular, methicillin (meticillin)-resistant S. aureus (MRSA) strains have been detected worldwide (15), and the prevalence of MRSA varies among countries and health institutions (2,4,27). The emergence of MRSA strains resistant to glycopeptides, as well as the increasing prevalence in the community (7), highlights the need for worldwide epidemiological studies of this pathogen. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
36
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 27 publications
11
36
2
Order By: Relevance
“…PVL is a necrotizing cytotoxin which is specific for the human and rabbit polymorphonuclear cells [20], which may be responsible for the Staphylococcal invasiveness and virulence. In developing countries like India [19,21], Africa [22] and other Asian countries [23], the prevalence rate of the pvl positive CA-MRSA is very high as compared to those at other geographic locations [17,24]. Even in this study, about 12% of the MSSA and 40% of the MRSA were found to be positive for PVL, which was slightly higher than that which was reported from other geographical regions and lower than the reports from Africa and India.…”
Section: Discussioncontrasting
confidence: 55%
“…PVL is a necrotizing cytotoxin which is specific for the human and rabbit polymorphonuclear cells [20], which may be responsible for the Staphylococcal invasiveness and virulence. In developing countries like India [19,21], Africa [22] and other Asian countries [23], the prevalence rate of the pvl positive CA-MRSA is very high as compared to those at other geographic locations [17,24]. Even in this study, about 12% of the MSSA and 40% of the MRSA were found to be positive for PVL, which was slightly higher than that which was reported from other geographical regions and lower than the reports from Africa and India.…”
Section: Discussioncontrasting
confidence: 55%
“…MRSA has become a major public health problem worldwide and recent reports have indicated that the prevalence of hospital -associated MRSA in health care institutions in Nigeria may vary from 1.5% to 20% (Okon et al, 2009). In this study, screening for MRSA revealed a prevalence rate of 13% which agrees with a study conducted in north-eastern Nigeria by Okon et al (2013) who reported a prevalence of 12.5%.…”
Section: Discussionsupporting
confidence: 89%
“…Also, a number of investigations have reported that Staphylococcus aureus is among the most frequently encountered bacterial species in microbiology laboratories in Nigeria (Okon et al, 2009;Odetoyin et al, 2008;Ubani, 2009). For effective treatment of Staphylococcus aureus infections, adequate information and data on susceptibility patterns and characterization of the organism are of great importance (Esan et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This strain of S. aureus has been reported virtually in all the countries of the world with varying frequencies (Dufour et al, 2002;Kesah et al, 2003;Crum et al, 2006). Nigeria has not been exempted from the global epidemic strain (Ghebremedhin et al, 2009;Okon et al, 2009;Alli et al, 2012). The gene encoding the MRSA phenotype has been linked to mecA gene on the chromosome that encodes a modified penicillin binding protein 2 (PBP2).…”
Section: Introductionmentioning
confidence: 99%